O Niilismo Alemão - Rodrigues, Eli Vagner Francisco (Voluntas: Revista Internacional de Filosofia, 2022)
Palestra proferida pelo Prof. Leo Strauss no General Seminar of the Graduate Faculty of Political and Social Science of the New School for Social Research in New York em fevereiro de 1941 editado pelos professores David Janssens (Vrije Universiteit Brussel) e Daniel Tanguay (University of Ottawa) e publicado na revista Interpretation A Journal of Political Philosophy Spring 1999 Volume 26 Number 3.